We have the functions \( p(x) = x^2 - 1 \) and \( q(x) = 5(x - 1) \).
To find the expression for \( (p - q)(x) \), we need to compute \( p(x) - q(x) \).
First, we can compute \( q(x) \):
\[ q(x) = 5(x - 1) = 5x - 5 \]
Now we can substitute \( p(x) \) and \( q(x) \) into \( (p - q)(x) \):
\[ (p - q)(x) = p(x) - q(x) = (x^2 - 1) - (5x - 5) \]
Now, we will simplify this expression:
\[ (p - q)(x) = x^2 - 1 - 5x + 5 \] \[ = x^2 - 5x + 4 \]
Now we can compare this with the options given:
- \( 5(x - 1) - x^2 - 1 \)
- \( (5x - 1) - (x^2 - 1) \)
- \( (x^2 - 1) - 5(x - 1) \)
- \( (x^2 - 1) - 5x - 1 \)
Now let's check \( (p - q)(x) = x^2 - 5x + 4 \) against the options:
-
For Option 1: \[ 5(x - 1) - (x^2 - 1) = 5x - 5 - x^2 + 1 = -x^2 + 5x - 4 \]
-
For Option 2: \[ (5x - 1) - (x^2 - 1) = 5x - 1 - x^2 + 1 = -x^2 + 5x \]
-
For Option 3: \[ (x^2 - 1) - 5(x - 1) = x^2 - 1 - 5x + 5 = x^2 - 5x + 4 \]
-
For Option 4: \[ (x^2 - 1) - 5x - 1 = x^2 - 1 - 5x - 1 = x^2 - 5x - 2 \]
The expression that matches \( (p - q)(x) = x^2 - 5x + 4 \) is the third option:
Answer: (x^2 - 1) - 5(x - 1)